Utilization of services rendered in dental outreach programs in rural areas of Haryana - Shelja Vashisth; Nidhi Gupta; Mohit Bansal; Nanak C Rao (Contemporary Clinical Dentistry, 2012)
Background: The availability of oral health services are very scarce in rural India; therefore the unmet treatment needs of rural population are very high. Hence, a retrospective study was conducted to evaluate the types of patients, disease pattern, and services rendered in outreach programs in rural areas of Haryana. Materials and Methods: A The data were obtained from records of outreach programs conducted, in last 3 months, by Swami Devi Dyal Hospital and Dental College. The data from were analyzed using descriptive statistics. Results: A total of 1371 individuals in the age group of 4--70 years (56.8% males and 43.2% females) attended the outreach program seeking the treatment. Dental caries (43.7%), gingivitis (27.2%), and periodontitis (22.9%) were commonly observed dental diseases. The services provided were oral prophylaxis (51.2%), restoration (22.9%), referral (20%), and extractions (8.8%). Conclusion: The attendance and utilization of dental services in the out reach programs seem to be influenced by sociodemographic characteristics of the population.